The Effect of Service Quality and Price Perception on Customer Satisfaction and Loyalty: A Study on Beauty Centers Operating in Erzurum - Sola, Fatma Gül Yazıcılar; Güzel, Dilşad; Şimşek, Tuba (Fırat University, 2023)
Nowadays, not only women but also men pay attention to their personal care. This situation affects the importance of beauty centers regarding personal care. Companies in the sector will increase their competitiveness if they offer quality services to the relevant market at low prices, ensuring customer satisfaction and gaining customer loyalty. In this direction, the aim of the study is to determine the effect of service quality and price perception on customer satisfaction and loyalty in beauty centers located in Erzurum city center. Service quality and price perception, which have been discussed many times in the literature in the context of their positive effects on customer loyalty, were determined as the independent variables of the research. In order to reveal this relationship in a more clear and purified way, the main problematic of the study was determined as whether the customer satisfaction variable, which is assumed to form the basis for customer loyalty, has an effect on this relationship. In this context, investigating the mediating effect of the customer satisfaction variable on the effect of service quality and price perception on customer loyalty constitutes the main research subject of the study. 400 surveys created for this purpose were applied online and face to face to consumers benefiting from beauty centers in Erzurum city center in December 2022 and February 2022. The obtained data were subjected to frequency analysis, reliability analysis, Wann Whitney U test, Kruskal Wallis test and regression analysis with the help of SPSS 28.00 package program and the results were interpreted. Additionally, a mediation analysis was conducted in the study to determine mediation effects. As a result of the analyses, it was determined that customer satisfaction has separate mediating effects on the effect of service quality and price perception on customer loyalty.

Günümüzde sadece kadınlar değil aynı zamanda erkekler de kişisel bakımlarına dikkat etmektedirler. Bu durum kişisel bakım ile ilgili olarak güzellik merkezlerinin önemini etkilemektedir. Sektörde yer alan firmaların kaliteli hizmetleri düşük fiyatlar ile müşteri memnuniyetini sağlayacak ve müşteri sadakatini kazanacak şekilde ilgili pazara sunmaları rekabet edebilirliklerini artıracaktır. Bu doğrultuda çalışmanın amacı Erzurum il merkezinde bulunan güzellik merkezlerinde hizmet kalitesi ve fiyat algısının müşteri memnuniyeti ve sadakati üzerindeki etkisini belirlemektir. Alanyazında müşteri sadakatine olan pozitif etkileri bağlamında birçok defa ele alınmış olan hizmet kalitesi ve fiyat algısı araştırmanın bağımsız değişkenleri olarak belirlenmiştir. Bu ilişkinin daha açık ve saflaştırılmış bir biçimde ortaya çıkarılabilmesi amacıyla da müşteri sadakatinin gerçekleşmesine zemin oluşturduğu varsayılan müşteri memnuniyeti değişkeninin bu ilişkide bir etkiye sahip olup olmadığı çalışmanın ana sorunsalı olarak belirlenmiştir. Bu bağlamda hizmet kalitesi ve fiyat algısının müşteri sadakatine olan etkisinde müşteri memnuniyeti değişkeninin aracılık etkisinin araştırılması çalışmanın ana araştırma konusunu teşkil etmektedir. Bu amaçla oluşturulan 400 anket, Erzurum il merkezinde bulunan güzellik merkezlerinden faydalanan tüketicilere 2022 Aralık ve 2022 Şubat aylarında çevrimiçi ve yüz yüze olarak uygulanmıştır. Elde edilen veriler SPSS 28.00 paket programı yardımıyla, frekans analizi, güvenilirlik analizi, Wann Whitney U testi, Kruskal Wallis testi ve regresyon analizine tabi tutulmuş ve sonuçlar yorumlanmıştır. Ayrıca çalışmada aracılık etkilerinin tespiti amacıyla aracılık analizi yapılmıştır. Yapılan analizler neticesinde hizmet kalitesi ve fiyat algısının müşteri sadakatine etkisinde müşteri memnuniyetinin ayrı ayrı aracılık etkilerinin söz konusu olduğu tespit edilmiştir.
HİZMET KALİTESİ VE FİYAT ALGISININ MÜŞTERİ MEMNUNİYETİ VE SADAKATİ ÜZERİNDEKİ ETKİSİ: ERZURUM’DA FAALİYET GÖSTEREN GÜZELLİK MERKEZLERİ ÜZERİNE BİR ARAŞTIRMA
Keywords: Microfinance; Mikrofinans